Global trends in the formation of professors - Zinabeddine ABDELHAFID (Social Sciences Journal, 1970)
The development of any community is ,undoubtedly, related strongly to the quality of itseducational system,and that happens through its effective contributions to prepare people to bearresponsibilities which, in turn,leads to the development of communities in differentfields.Therefore,different countries sought to develop the infrastructures represented by theeducational organizations in which people can have the opportunity to receive their training andpreparation ,and since the teacher is the corner stone of the educational system,they also sought totrain and prepare him through different training programmes relative to the cognitive,cultural andeducational aspects. the growing number of research in the educational field, has lead to theappearance of the diversity of the international trends intended for teacher preparation, in additionto the diversity of the related programmes.This study aims at mentioning the most eminent trends ,teacher preparation programmes and their related systems